Perioperative management during laparoscopic resection of large pheochromocytomas: A single‐institution retrospective study. Issue 4 (2nd September 2018) - Liu, Hongju; Li, Bin; Yu, Xuerong; Huang, Yuguang
Abstract : Background and Objectives: The safety of laparoscopic resection of very large pheochromocytomas is unclear, and preoperative preparation may benefit from refinement. This retrospective study was designed to determine the correlation between tumor size and perioperative characteristics by evaluating data from patients who underwent laparoscopic resection of pheochromocytomas. Methods: A total of 253 patients were grouped according to their tumor diameter: diameter ≥8 cm, Glarge (Glg ) ( n  = 30); diameter 6 to 8 cm, Gmedium (Gmd ) ( n  = 57); and diameter <6 cm, Gsmall (Gsm ) ( n  = 166). The perioperative data were compared among the three groups using the analysis of variance test, Wilcoxon's rank‐sum test, and the chi‐square test. Results: Patients in the Glg and Gmd groups had a higher preoperative phenoxybenzamine daily dose and 24‐hour urine levels of noradrenaline and adrenaline than those in the Gsm group, as they needed longer vasopressor support. Transfusion of allogeneic blood products was found to be increased in patients of the Glg group compared with the other two groups and their intensive care unit stays were longer. Conclusions: Compared with small‐sized pheochromocytomas, laparoscopic resection of medium‐sized pheochromocytomas requires vigilant monitoring and resolution of hemodynamic fluctuations. Patients with very large pheochromocytomas are at greater risk of intraoperative bleeding and may benefit from the ensured availability of blood products and intensive postoperative monitoring.